Radiation belt seed population and its association with the relativistic electron dynamics: A statistical study. Issue 5 (19th May 2017) - Tang, C. L.; Wang, Y. X.; Ni, B.; Zhang, J.‐C.; Reeves, G. D.; Su, Z. P.; Baker, D. N.; Spence, H. E.; Funsten, H. O.; Blake, J. B.
Abstract: Using the particle data measured by Van Allen Probe A from October 2012 to March 2016, we investigate in detail the radiation belt seed population and its association with the relativistic electron dynamics during 74 geomagnetic storms. The period of the storm recovery phase was limited to 72 h. The statistical study shows that geomagnetic storms and substorms play important roles in the radiation belt seed population (336 keV electrons) dynamics. Based on the flux changes of 1 MeV electrons before and after the storm peak, these storm events are divided into two groups of "large flux enhancement" and "small flux enhancement." For large flux enhancement storm events, the correlation coefficients between the peak flux location of the seed population and those of relativistic electrons (592 keV, 1 MeV, 1.8 MeV, and 2.1 MeV) during the storm recovery phase decrease with electron kinetic energy, being 0.92, 0.68, 0.49, and 0.39, respectively. The correlation coefficients between the peak flux of the seed population and those of relativistic electrons are 0.92, 0.81, 0.75, and 0.73. For small flux enhancement storm events, the correlation coefficients between the peak flux location of the seed population and those of relativistic electrons are relatively smaller, while the peak flux of the seed population is well correlated with those of relativistic electrons (correlation coefficients >0.84). It is suggested that during geomagnetic storms there is a good correlation between the seed population and ≤1 MeV electrons and the seed population is important to the relativistic electron dynamics. Key Points: Geomagnetic storms and substorms play important roles in the radiation belt seed population dynamics The radiation belt seed population is well correlated with ≤1 MeV electrons The radiation belt seed population is important to the relativistic electron dynamics